Efektivitas Ozonated Virgin Coconut Oil Dosis Bertingkat Terhadap Penyembuhan Luka Full Thickness Skin Graft Autolog Ditinjau Dari Jumlah Fibroblas Dan Ekspresi Vascular Endothelial Growth Factor Pada Tikus Sprague Dawley - Napitupulu, Johan Rinto Even; Hardian, Hardian; Najatullah, Najatullah (RSUP Dr. Kariadi, 2021)
Abstract Background: Now, Skin grafts are one of the therapies of choice in the wound healing process. And this is still developing today. The process of formation fibroblas and the formation of vascular endothelial growth factor have an important role in healing skin graft wounds. Ozonated virgin coconut oil has an important role in wound healing. Objective: To prove the effect of ozonated virgin coconut oil in various doses in increasing number of fibroblas and expression of vascular endothelial growth factor of skin graft wounds. Methods: This study is an experimental study with